Psychology for teachers - Buckler, Scott; Castle, Paul (Sports psychologist) (Los Angeles : SAGE, 2018)
Every child is an individual whose knowledge and understanding needs to be developed in ways that help them succeed. How do you manage this alongside the realities of the curriculum? How do you achieve this for a full classroom of expectant learners? This book explains how psychology can be intelligently applied to the classroom to meet the needs of different learners. It encourages you to review your own practice to develop a personal teaching style, supported by research findings and an awareness of the factors underpinning high-quality teaching. Focusing on how an understanding of psychological theory can support effective teaching and learning this book contains case studies and tasks to make sure that you really understand how theory can be meaningfully applied in the classroom.
Includes bibliographical references : pages [469]-505 and index.
Keywords: School psychology; Teaching -- Psychological aspects; Educational psychology